Team Effectiveness of Nursing Instructors under The Ministry of Public Health - มโนการ, ชูศรี; บัวผุด, ศศิญา; ใจยะสิทธิ์, รัศมิ์ลภัส (Journal of The Royal Thai Army Nurses, 2019)
The research was quantitative research to study the team effectiveness of nursing instructors under the Ministry of Public Health. A sample of 325 was randomly selected from nursing instructors under the Ministry of Public Health. The research instrument was a questionnaire which used to collect data were (i) a personal information questionnaire; (ii) an opinion of emotional intelligence and individual characteristics; (iii) an opinion of servant leadership; and (iv) an opinion of team effectiveness. The data were analyzed using descriptive statistics. Findings revealed that team effectiveness of nursing instructors under the Ministry of Public Health was a high level ( = 4.14). The team relationships and team problem-solving were highest level ( = 4.20), and team members, team leader, and organizational environment ( = 4.19, 4.14, 3.88 respectively).